Livelihood Strategies of Salt Farmer Communities in Facing Climate Variability - Sofia Tunnida; Ibnu Phonna Nurdin (Pusat Riset dan Inovasi Nasional, 2025)
Salt farming requires stable climate conditions to be able to produce salt sustainably. However, currently, the negative impact of climate variability on salt farming areas is very significant. This affects the sustainability of the salt farming efforts of farmers at the research location. The purpose of this research is to describe the impact of climate variability on the salt farmer community and the livelihood strategies of salt farmers in facing climate variability in Gampong Ara, Kembang Tanjong District, Pidie Regency. This research uses the Livelihood Strategy theory. The method used in this research is descriptive qualitative with a case study approach. Data were collected through observation, interviews, and documentation. The determination of informants in this study are salt farmers who have worked as farmers for at least 10 years. After the data is collected, a data analysis technique is performed, which includes data reduction, data presentation, and conclusion drawing. The results of this study show that the salt farmer community is facing a very difficult situation due to climate variability. The impacts caused include: 1. High rainfall, 2. Difficulty in producing salt during strong winds, 3. Full moon tides, and 4. Flooding of land during the rainy season. Therefore, farmers developed adaptation strategies in the form of livelihood strategies at the research location, namely: land intensification and extensification, as well as livelihood diversification. Intensification of capital addition for salt farmers, such as firewood, and extensification for farmers to increase labor, and diversification carried out by salt farmers to seek other jobs besides agriculture to temporarily replace their main work. The support of policymakers is greatly needed by the salt farmer community to bolster the resilience of farmers in maintaining their sustainability.